Harmonic elimination by switching angle optimization technique for multilevel inverter - Altayib Sahhouk, Masoud Albasheer (2019)
The needs for a free harmonic and high rating power source is increased to meet the required industry applications. In this project, a 7-level Cascaded H-Bridge Multilevel Inverter (CHBMLI) with two various controllers are presented. Proportional Integral (PI) and Artificial Neural Network (ANN) controllers are used to improve the performance of output voltage and a low level of total harmonic distortion (THD). A pulse width modulation generators have been connected to switching devices of 7-level CHBMLI. The reference waveform for pulse width modulation (PWM) generator is considered to be a sinusoidal wave to obtain ideal AC output voltage waveform from the CHBMLI. By tuning the PI controller as well as the self-learning abilities of the ANN controller, switching signals towards the CHBMLI can be improved. This project is to provide a model of the multilevel inverter using 7-level CHBMLI DC-AC converter to reduce THD. The simulation results with using the PI controller and ANN controller to reduce THDs have been compared and discussed. By implementing the controllers, the THDs are reduced from 24.72% to 4.09% with PI controller, while with ANN controller, the THD further reduced by 3.16%.